2020
DOI: 10.1111/ene.14497
|View full text |Cite
|
Sign up to set email alerts
|

Cranial nerve involvement in typical and atypical chronic inflammatory demyelinating polyneuropathies

Abstract: Background and purpose Cranial nerve palsy is occasionally present in patients with chronic inflammatory demyelinating polyneuropathy (CIDP), but its prevalence, characteristics and relations with the CIDP subtypes have rarely been investigated. The aim of this study was to systematically assess cranial nerve involvement in typical and atypical CIDP. Methods Clinical data were reviewed in 132 consecutive patients with CIDP, including typical CIDP (n = 89), multifocal acquired demyelinating sensory and motor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 18 publications
(16 reference statements)
2
22
0
Order By: Relevance
“…One notable feature in the present case was cranial nerve involvement, which included the facial and hypoglossal nerves. Cranial neuropathy is clinically uncommon in patients with CIDP, although it has been described in several case series or reports, including in cranial nerves II to X, and XII [ 2 , 3 , 8 11 ] (Table 2 ). A review of the literature revealed a reported incidence of cranial nerve involvement in 5% to 20% of patients with CIDP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One notable feature in the present case was cranial nerve involvement, which included the facial and hypoglossal nerves. Cranial neuropathy is clinically uncommon in patients with CIDP, although it has been described in several case series or reports, including in cranial nerves II to X, and XII [ 2 , 3 , 8 11 ] (Table 2 ). A review of the literature revealed a reported incidence of cranial nerve involvement in 5% to 20% of patients with CIDP.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed a reported incidence of cranial nerve involvement in 5% to 20% of patients with CIDP. According to a retrospective study, cranial palsy is frequent in MADSAM (48%), but less frequent in typical CIDP (11%) and distal acquired demyelinating symmetric (11%) [ 3 ]. Facial paralysis is the most common involved, followed by bulbar involvement and oculomotor nerve paralysis [ 3 , 8 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations